الحكومة الإلكترونية في الجزائر دراسة مقارنة بدول شمال إفريقيا -: E-government in Algeria - a comparative study with North African countries - سميرة صالحي; ناصر يوسف; إيمان بن الزين (Journal of North African Economies, 2025)
This research paper aims to present Algeria’s experience in the field of e-government and compare it with North African countries, Tunisia, Morocco and Egypt, in order to assess its situation at the regional level. The comparison was made based on the e-government development index (EGDI) issued by the United Nations, which includes the infrastructure sub-index (TII), human capital sub-index (HCI) and e-government service sub-index (OSI), in the period between 2008 and 2020. the aim of this comparison is taking advantage from the experiences of these countries and learning lessons to face the challenges, and use the opportunities available to Algeria to develop its e-government, and to keep pace with the global movement and to increase its efficiency to serve the goals of sustainable development. The study concluded that e-government is not a website despite its importance, and it is not computers located in government agencies despite their necessity. It is a complete restructuring of the government apparatus, or a rediscovery of the role and procedures of government to be more effective and efficient; The study also found that the e-government project in Algeria faces many obstacles and major challenges that prevented its progress.